Interprofessional Learning as Work-integrated Learning:: When Dialogues about Databases and Information Literacy create a platform for Learning - Näverå, Elisabeth; Spante, Maria (Nordic Journal of Information Literacy in Higher Education, 2019)
Team Research Support and Publishing at University West’s Library consists of four librarians who guide researchers and doctoral students in issues regarding publishing strategies, bibliometrics, Information Literacy and how to make research publications available e.g. in the local repository DiVA. The service is frequently used in several ways by various researchers in accordance with their special needs. The case is originally based on three meetings between a librarian and a researcher entailing individual texts of reflections. This presentation accentuates the benefits of the discussions through the perspectives of collaborative learning and work-integrated learning. These benefits will thus be highlighted through the experiences from continuous face-to-face appointments with focus on information seeking activities and the effective use of databases. The meetings between the librarian and the researcher are affected by the fact that both work categories bring their specific professional competences into the discussions. In the dialogues they thus become each other’s teachers as well as students. The mixed situation of being the bearer of both roles simultaneously is dealt with by the interacting participants and the co-created meetings are carried through, and filled with contents, by the professionals themselves. Furthermore, this case emphasizes as well as problematizes this situation starting off from the individual professionals points of view. Finally, this study recommends the university management to encourage as well as create conditions for further interprofessional encounters at work in order to support Work-integrated learning in and for the organization.